Adults show selective responses to unreliability based on the strength of counterevidence - Kirsten H. Blakey; Giacomo Melis; Zsófia Virányi; Eva Rafetseder (PLoS ONE, 2025)
Adults can reflectively revise their beliefs and selectively respond to unreliable informants, despite often forming and revising beliefs unreflectively without assessing their reasons. This study investigates how the strength of counterevidence coming from an informant affects adults’ ability to infer that the informant is unreliable through acquiring and responding to undermining defeaters (i.e., evidence suggesting that something was wrong with how the belief was formed). Participants ( N = 120) watched videos of two informants acting on two locations: one whose actions reliably indicated the reward location, and one whose actions did not. The strength of feedback participants received after making a choice was manipulated across two conditions. In the Strong feedback condition, participants received positive feedback when they found the reward and explicit negative feedback when they did not, along with information about the reward’s true location. In the Weak feedback condition, they received positive feedback, but incorrect choices simply resulted in no reward. Participants responded selectively to unreliability, following the Unreliable informant’s evidence less often than that of the Reliable informant. This effect was stronger in the Strong feedback condition and was observed after only two to three misleading trials. In subsequent trials where informants were pitted against each other, participants in the Strong feedback condition, but not in the Weak feedback condition, consistently preferred the Reliable informant. These findings suggest that adults’ ability to infer informants’ reliability depends on the strength of counterevidence. Additionally, exploratory analyses reveal a key distinction between acquiring and responding to undermining defeaters.